2007
DOI: 10.1016/j.jasms.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Validated MALDI-TOF/TOF mass spectra for protein standards

Abstract: A current focus of proteomics research is the establishment of acceptable confidence measures in the assignment of protein identifications in an unknown sample. Development of new algorithmic approaches would greatly benefit from a standard reference set of spectra for known proteins for the purpose of testing and training. Here we describe an openly available library of mass spectra generated on an ABI 4700 MALDI TOF/TOF from 246 known, individually purified and trypsin-digested protein samples. The initial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 21 publications
1
57
0
Order By: Relevance
“…Hence the commercially purified standard proteins from bovine, chicken, rabbit, horse, Bacillus lichenformis, yeast and Escherichia coli (Keller et al, 2002b) might each contain more than 0.01% of hundreds of copurifying proteins and this would explain that upon analysis by LC-MS/MS, the small minority of spectra showed high scores that correlated to the 18 purified proteins, but the vast majority of spectra did not match the purified targets (Keller et al, 2002b). In this regard, a set of cloned human proteins expressed in E. coli and highly purified by affinity chromatography showed that half the tandem spectra collected were correctly assigned to the specific set of recombinant proteins with the remainder presumably from the E. coli host (Falkner et al, 2007). Furthermore a more accurate estimate of instrument reliability might be obtained by analyzing a well-defined mixture of very high purity, such as purified viral proteins (Chelius et al, 2002).…”
Section: Specificity Of Lc-ms/ms Of Bloodmentioning
confidence: 99%
“…Hence the commercially purified standard proteins from bovine, chicken, rabbit, horse, Bacillus lichenformis, yeast and Escherichia coli (Keller et al, 2002b) might each contain more than 0.01% of hundreds of copurifying proteins and this would explain that upon analysis by LC-MS/MS, the small minority of spectra showed high scores that correlated to the 18 purified proteins, but the vast majority of spectra did not match the purified targets (Keller et al, 2002b). In this regard, a set of cloned human proteins expressed in E. coli and highly purified by affinity chromatography showed that half the tandem spectra collected were correctly assigned to the specific set of recombinant proteins with the remainder presumably from the E. coli host (Falkner et al, 2007). Furthermore a more accurate estimate of instrument reliability might be obtained by analyzing a well-defined mixture of very high purity, such as purified viral proteins (Chelius et al, 2002).…”
Section: Specificity Of Lc-ms/ms Of Bloodmentioning
confidence: 99%
“…4E). Purified NicA was analyzed further by matrix-assisted laser desorption ionization-time of flight mass spectrometry using peptide mass fingerprinting techniques for an array of peptide masses resulting from enzymatic digestion of the protein isolated from an SDS-PAGE gel (8). The two digested peptides were both identical to the translation products of nicA gene fragments (for DAEKSFTR the MASCOT ion score was 41.4191; for LLSMSP YLTR, the Mascot ion score was 43.3286) (see Fig.…”
Section: Vol 75 2009mentioning
confidence: 99%
“…In such a case, no gas was added to the collision cell; only variation of the laser fluence in the ion source was employed to trigger the dissociation processes according to metastable fragmentation in a field free region [52]. Given the availability of both LID and LID/ CID high energy dissociation regimes, MALDI-TOF/TOF constitutes a major versatile analytical tool in proteomics [53,54] and more generally in any field requiring high throughput analyses [55]. The same results were obtained under all dissociation conditions as depicted in Table 1.…”
Section: Influence Of Precursor Ion Activation Methods On C-terminal Rmentioning
confidence: 99%